2012
DOI: 10.1007/s12665-012-2146-5
|View full text |Cite
|
Sign up to set email alerts
|

Topographic controls on vegetation index in a hilly landscape: a case study in the Jiaodong Peninsula, eastern China

Abstract: This study examined topographic influence on spatial and temporal variability in the normalized difference vegetation index (NDVI) derived from the Satellite Pour l'Observation de la Terre-Vegetation at the regional and landscape scales in the Jiaodong Peninsula. The generalized additive models were used to quantify the spatial variation of NDVI attributable to local terrain and topographically related variables including altitude, exposure to incoming solar radiation, topographic wetness index, distance to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Based on this rationale, most studies consider that band ratio VIs (for example, the Normalized Difference Vegetation Index -NDVI) can overcome topographic effects on radiometric levels (Lee and Kaufman, 1986;Ekstrand, 1996;Huete at al., 1999). However, some studies showed that topography significantly affects VIs in rugged mountainous area (Verbyla et al, 2008;Veraverbeke et al, 2010;Wang et al, 2012). For example, Deng et al (2007) observed that the NDVI and the Normalized Difference Infrared Index (NDII) showed a significant correlation (r 2 ) (p = 0.001) with topography variables such as slope and the cosine of the aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this rationale, most studies consider that band ratio VIs (for example, the Normalized Difference Vegetation Index -NDVI) can overcome topographic effects on radiometric levels (Lee and Kaufman, 1986;Ekstrand, 1996;Huete at al., 1999). However, some studies showed that topography significantly affects VIs in rugged mountainous area (Verbyla et al, 2008;Veraverbeke et al, 2010;Wang et al, 2012). For example, Deng et al (2007) observed that the NDVI and the Normalized Difference Infrared Index (NDII) showed a significant correlation (r 2 ) (p = 0.001) with topography variables such as slope and the cosine of the aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Natural population growth and migration can result in urban expansion, reduced vegetative cover, and frequent changes in land use. Anthropogenic activity contributes to increased water use and elevated greenhouse gas emissions, affecting urban climate factors such as temperature, humidity, and aridity [69][70][71]. Elevation has a significant influence on factors such as rainfall distribution, temperature, radiation intensity, soil quality, plant ecology, growth, and overall ecological quality.…”
Section: Rsei Response To Spatial Scalesmentioning
confidence: 99%
“…A primary cause for this is rugged topography, except few areas in different parts of the watershed. Some studies showed that topography significantly affects VIs in a rugged mountainous area (Veraverbeke et al, 2010;Verbyla et al, 2008;Wang et al, 2012). Deng et al (2007) observed that the NDVI and the Normalized Difference Infrared Index (NDII) showed a significant correlation (r 2 ) (p = 0.001) with topography variables such as slope and the cosine of the aspect.…”
Section: Vegetation Indices Ndvi and Ndwimentioning
confidence: 99%